Lethal Effect of Diode Laser on the Bacteria Pseudomonas aerugiosa Isolated from wounds - Yasir K. Mohammed (Journal of Madenat Alelem University College, 2010)
The study Diode Laser with power of (120) mw and (650) wavelength and power density (1123.234) W/cm2 continues (CW) . Also shows that the expose of the sample of bacteria Pseudomonas aerugiosa to Diode Laser after focal point in lens of focal point (10) cm for periods of time (5,10,15,20,25) min. This study is prove effectiveness violent of bacteria Pseudomonas aerugiosa.